Sestrin-2 as a Diagnostic Potential Biomarker for Diabetic Kidney Disease in Individuals with Type 2 Diabetes mellitus - Asaad Munaf Mustafa; Eham Amer Ali; Abbas Mahdi Rahmah (Karbala Journal of Medicine, 2025)
Background: Diabetic kidney disease (DKD) is a major microvascular complication of type 2 diabetes mellitus (T2DM), contributing significantly to end-stage renal disease. Sestrin-2 (SESN2), a protein induced by stress that plays a role in oxidative stress response, autophagy, and metabolic control, has been identified as a potential biomarker candidate. Methods: A case-control study involved one hundred and sixty patients who were diagnosed with T2DM. Blood analysis for sugar levels (FBG and HbA1c), lipid profile, renal function test, and albumin-to-creatinine ratio in urine (uACR) were assessed. Results: The serum sestrin-2 levels were significantly elevated in patients with T2DM compared to healthy controls. Macroalbuminuria patients showed the highest sestrin-2 level (3.28 ± 1.22 ng/ml). However, the serum levels of sestrin-2 in the health group were (2.29 ± 0.59 ng/ml), in the normoalbuminuria group, there was a significant positive correlation between serum sestrin-2 levels with FBG, HbA1c, and High-density lipoprotein (HDL), and a negative correlation between sestrin-2 and glomerular filtration rate (GFR). Moreover, in the microalbuminuria group, a significant positive correlation of a moderate effect size was observed between sestrin-2 level with body mass index (BMI). The area under the receiver operating characteristic curve (AUC) for Sestrin-2 was 0.933 at the cutoff value 3.91, with the sensitivity and specificity for differentiating macroalbuminuria from control being 100% and 75%, respectively. Conclusions: The serum concentrations of sestrin-2 were markedly elevated in the study groups (normoalbuminuria, microalbuminuria, and macroalbuminuria) compared to the healthy control group, suggesting its involvement in the development of diabetic kidney disease (DKD) as a complication of T2DM. Based on the findings, Sestrin-2 demonstrates a remarkable capacity for diagnosing DKD.